MANGGAR DAM RISK ASSESSMENT BASED ON THE ANDERSEN MODIFICATION METHOD - Yudha Pratama Narra Putra; Ignatius Sriyana; Suprapto Suprapto (Jurnal Ekonomi, 2023)
Dams are massive water structures built for a spesific purpose, usually used for irrigation, raw water, flood control, and hydropower. Besides having great benefits also have the potential for failure as well. With such a large failure potential, the dam must continue to be monitored and maintained by carrying out Routine Operation and Maintenance activities. With the data obtained during the operation and Maintenance activites, we can anticipate the potential dam failure by conducting a Risk Assessment. Risk Assessment is used to determine repair and rehabilitation priorities that are balanced with budget availability and restore the service function of the dam. Manggar Dam is a dam that built by damming the Manngar Besar River. The Manggar Dam is located on the Manggar Besar River under the River Basin Unit (BWS) Kalimantan III in East Kalimantan Province. The method used in this research is Modified Andersen, wich is based on technical characteristics, safety plans, and the existing conditions of the dam. Using Inspection data that BWS Kalimantan III and Dam Office get. With visual inspections in the field, results of major inspection reports, and other technical documents. The results of this study indicate that the Manggar Dam is an old dam that has been repaired and built to enlarge its capacity. With the Andersen Modification method, the Manggar Dam gets a Total Risk Index Score (IRtot) of 19, wich means that the dam is in good condition and has a low risk of failure. There are only a few improvements that need to be made.